Klebsiella pneumoniae Carbapenemase Variants Resistant to Ceftazidime-Avibactam: an Evolutionary Overview - Hobson, Claire Amaris; Pierrat, Gautier; Tenaillon, Olivier; Bonacorsi, Stéphane; Bercot, Béatrice; Jaouen, Ella; Jacquier, Hervé; Birgy, André (Antimicrobial agents and chemotherapy, 2022)
First variants of the Klebsiella pneumoniae carbapenemase (KPC), KPC-2 and KPC-3, have encountered a worldwide success, particularly in K. pneumoniae isolates. These beta-lactamases conferred resistance to most beta-lactams including carbapenems but remained susceptible to new beta-lactam/beta-lactamase inhibitors, such as ceftazidime-avibactam. First variants of the Klebsiella pneumoniae carbapenemase (KPC), KPC-2 and KPC-3, have encountered a worldwide success, particularly in K. pneumoniae isolates. These beta-lactamases conferred resistance to most beta-lactams including carbapenems but remained susceptible to new beta-lactam/beta-lactamase inhibitors, such as ceftazidime-avibactam. After the marketing of ceftazidime-avibactam, numerous variants of KPC resistant to this association have been described among isolates recovered from clinical samples or derived from experimental studies. In KPC variants resistant to ceftazidime-avibactam, point mutations, insertions and/or deletions have been described in various hot spots. Deciphering the impact of these mutations is crucial, not only from a therapeutic point of view, but also to follow the evolution in time and space of KPC variants resistant to ceftazidime-avibactam. In this review, we describe the mutational landscape of the KPC beta-lactamase toward ceftazidime-avibactam resistance based on a multidisciplinary approach including epidemiology, microbiology, enzymology, and thermodynamics. We show that resistance is associated with three hot spots, with a high representation of insertions and deletions compared with other class A beta-lactamases. Moreover, extension of resistance to ceftazidime-avibactam is associated with a trade-off in the resistance to other beta-lactams and a decrease in enzyme stability. Nevertheless, the high natural stability of KPC could underlay the propensity of this enzyme to acquire in vivo mutations conferring resistance to ceftazidime-avibactam (CAZavi), particularly via insertions and deletions.